A model organism for genomic and postgenomic studies. - Bond, U.
In an era of automated DNA sequencing and revolutionary advances in DNA sequence analysis, the attention of many researchers is now shifting away from the study of single genes or small gene clusters to whole genome analyses. Knowing the complete sequence of a genome is only the first step in understanding how the myriad of information contained within the genes is transcribed and ultimately translated into functional proteins. In the postgenomic era, the goals are to obtain an image of the dynamic cell through functional genomic and proteomic studies. With its prominent position as the first eukaryotic genome to be completely sequenced and annotated, it is not surprising that research into the yeast Saccharomyces cerevisiae is leading the way in the development of biological and computational tools for genomic and postgenomic research. This article describes how databases concerning Saccharomyces cerevisiae can be mined to obtain important information on gene/genome expression and regulation under a variety of experimental conditions as well as the type, location, and function of proteins encoded by these genes
Keywords: Saccharomyces cerevisiae yeast; Automated DNA sequencing; Database mining; Eukaryotic genome; Functional proteins; Gene expression; Genome expression; Genomic studies; Model organism; Postgenomic studies